PENGUATAN PENDIDIKAN NILAI DI BIDANG FIQH; STUDI PEMIKIRAN FALAK KH. ABDUL RANI MAHMUD - Moch Riza Fahmi (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2015)
Values education is establishing noble values in a student by a teacher. Values education serves as a support to students to materialize and experience values, and integrate them in his/her whole life. KH. Abdul Rani Mahmud was an ulema and also a teacher at Madrasah al-Raudhatul Islamiyah Pontianak who devoted his life to Islamic education in Pontianak. His concept of Falakwas classical, similar to the method developed by earlier ulemas such as Kiai Ma’shum ibn Ali because he used refraction data, declination of the sun, and (standard) old version of equation of time, and did not include the calculation of altitude from the sea level, and determine the time of sunrise and sunset. However, in general his concept of falakin the calculation of the time of prayer is in accordance with astronomy using latitude and longitude data, equation of time, declination of the sun, altitude, and angle of the sun.